Recent Studies on Strawberries - Ebru Kafkas, Nesibe (IntechOpen, 2023)
This book discusses the following topics related to strawberry production: • Use of horizontal and vertical farming, machine learning and smart systems in strawberry production • Innovative techniques in strawberry production • Soilless farming techniques • Use of nature-friendly techniques to combat climate change, diseases and pests • Breeding and propagation by tissue culture • Responses of strawberries to photoperiod • Harvest and post-harvest processes • Benefits to human health We hope this book will be useful to all producers, breeders, and industrial operators who use strawberry products as raw materials in the food sector, and to researchers and students of horticulture.